Filogeografía y taxonomía de Xenotoca melanosoma Fitzsimons, 1972 (Cyprinodontiformes: Goodeidae) - Mar Silva, Adán Fernando (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
Xenotoca melanosome is restricted to the western region of central Mexico and it is dispersed in nine isolated basins from this area In the Ayuquila, Tamazula, Ameca and Etzatlán rivers, besides Magdalena, Atotonilco, Sayula Zapotlán and San Marcos lakes. The purpose of this study was to determine the phylogeographic pattern of the species. The specimens were collected in 13 localities where there were previous records of it. 96 sequences of the cytochrome b mitochondrial gene and 36 of the rhodopsin nuclear gene were used. The phylogenetic relationships obtained by Bayesian inference and maximum likelihood formed two main clades. The first consisting of the Ayuquila and Tamazula populations, which were called clade I. The clade II consisted of the populations of the lakes in western and Etzatlán and Ameca rivers. The haplotype network based in cytochrome b shows two independent haplogroups consistent with the main clades. Thirteen haplotypes of the mitochondrial gene were obtained, two for the clade I and eleven to clade II. With the nuclear gene we obtained the same main clades, however no haplotype network formed two independent haplogroups. Seven haplotypes were obtained, two belonging to clade I and five to clade II. Haplotype diversity values were higher in the clade II with a value of 0.738, while clade I has a value of 0.476. The values of D Tajima and F of Fu and Li indicated a constant effective population size. The population structure was explained mostly by the main clades with a value of ?st 0.971 p <0.05, and with a percentage of 82.60%. Mismatch distribution in clade I is bimodal, suggesting that the two populations are isolated in this clade. Conversely the Clade II shows a unimodal distribution suggesting a more recent contact between different populations.

La especie Xenotoca melanosoma, se encuentra restringida a la región occidental del centro de México y se distribuye en nueve cuencas aisladas de esta zona. En, los ríos Ayuquila, Tamazula, Ameca y Etzatlán, además de los lagos de Magdalena, Atotonilco, Sayula, Zapotlán y San Marcos. El presente estudio tuvo como finalidad determinar el patrón filogeográfico de la especie. Se colectó en 13 localidades que correspondieron a las cuencas donde se encuentra registrada la especie. Se obtuvieron 96 secuencias del gen mitocondrial Citocromo b y 36 del gen nuclear Rodopsina. Las relaciones filogenéticas obtenidas con inferencia Bayesiana y Máxima Verosimilitud, formaron dos clados principales; el primero conformado por las poblaciones de Ayuquila y Tamazula, que se considera clado I. El clado II está constituido por las poblaciones de los lagos de la zona occidental y los ríos de Ameca y Etzatlán. La red de haplotipos basada en Citocromo b, muestra dos haplogrupos independientes que concuerdan con los clados principales. Trece haplotipos fueron encontrados en las poblaciones, dos corresponden al clado I y los once están presentes en el clado II. Con el gen nuclear obtuvieron los mismos clados principales, sin embargo, la red de haplotipos no formó dos haplogrupos independientes. Se obtuvieron siete haplotipos, dos para el clado I y cinco para el clado II. El valor de diversidad haplotípica fue mayor en el caldo II con un valor de 0.738, mientras que el clado I tiene un valor de 0.476. Los valores de D Tajima y F de Fu y Li indicaron un tamaño efectivo poblacional constante. La estructura poblacional fue explicada en su mayor parte por los clados principales con un valor de Φst 0.971 p<0.05, y con un porcentaje del 82.60%.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2014-1458; Opción en ecología y conservación; Clados; Haplogrupos; Dimorfismo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1722